ศักยภาพของความกว้างฟันเขี้ยวในการจำแนกเพศคนไทยกลุ่มหนึ่ง - ทวีพงศ์ อารยะพิศิษฐ (2015)
Objective: To evaluate the sex dichotomy role of mesiodistal coronary dimension of canines in a group of Thais. Materials and methods: Three hundred and seventeen Thai subjects (163 males and 154 females) aged 18 to 22 years old who had fully-erupted, caries-free and non-worn upper as well as lower canines were randomly recruited. Maximum mesiodistal canine width of each canine was measured using digital vernier calipers. Potential sex difference of each canine was analyzed by t-test (α=.05), whereas the difference of left and right canines was determined by paired t-test (α=.05). Sexual dimorphism of each canine was also expressed as percent dimorphism. Results: All canine widths were significantly greater in male than in female (p<0.001), however, no significant difference between left and right canines was detected (p>0.05). Sexual dimorphism of lower canines was greater than upper canines. Conclusion: Significant difference between sexes was found in all canines, while the lower canines had more sexual dimorphism than the upper canines.